2023
DOI: 10.18632/aging.204923
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-related long non-coding RNAs AL359220.1, SH3BP5-AS1 and ZF-AS1 are significant for prognostic assessment of lung adenocarcinoma

Abstract: Background: Metastasis of lung adenocarcinoma (LUAD) severely worsens prognosis. Genetic alteration in the tumor microenvironment (TME) is closely associated with metastasis and other malignant biological properties of LUAD. In this study, we establish a metastasis-related risk model to accurately predict LUAD prognosis. Methods: RNA-sequencing profiles and clinical data of LUAD patients including 503 tumor tissues and 54 adjacent normal tissues were collected in TCGA database. Additionally, the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In some previous studies, researchers have found that SH3BP5-AS1 may be involved in the metastasis and aging process of tumor cells, thus affecting the clinical prognosis of lung adenocarcinoma patients [ 11 , 12 ]. There are also studies that show that SH3BP5-AS1 activated Wnt signaling pathway by sponging miR-139-5p, upregulating CTBP1 expression, and contributing to the sensitivity of pancreatic cancer cells to gemcitabine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies, researchers have found that SH3BP5-AS1 may be involved in the metastasis and aging process of tumor cells, thus affecting the clinical prognosis of lung adenocarcinoma patients [ 11 , 12 ]. There are also studies that show that SH3BP5-AS1 activated Wnt signaling pathway by sponging miR-139-5p, upregulating CTBP1 expression, and contributing to the sensitivity of pancreatic cancer cells to gemcitabine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%